The Reciprocal Effect Between Soil Water Content and The Soil Bulk Density on The Growth and Yield Of Onion (Allium Cepa L.) - Pou Anda (Green Engineering Society, 2021)
The SWC and the SBD play an important role in determining soil’s suitability for agricultural uses because they affect various physical, chemical, and biology of soil properties. This field experiment aimed to investigate the reciprocal effect of the SWC and the SBD on the growth and yield of onion (Allium cepa L.). The experiment was layout in a randomized complete block design (RCBD) with three replications. This experiment consisted of one factor, namely, water (A) with four levels, namely, (A0=0 liter, A1=4 liters, A2=8 liters, and A3=16 liters), and one variety endemic of local Tomia (V). The treatment consisted of A0V, A1V, A2V, and A3V. Parameters observed including plant height, leaf width, fresh bulb and dry bulb weight. The results showed that the different water levels treatment had a highly significant (p<0.01) affected the SWC and SBD. Also, simultaneously the SWC and the SBD had a high significance (p<0.01) reciprocally influenced the plant height, leaf width, fresh and dry weight of onion. When the SWC increase, the growth and the yield of onion increase, and when (SBD) decreases, the growing and the yield parameters increases. The best result occurred at the pair of SWC and SBD values of (28.52 %, 1.2 g.m3) with 33.07 cm plant height, 1.3 cm leaf width, 51.67 g fresh weight, and 44.33 g dry weight, followed by other pair of values of SWC and SBD. Through graphs, the analysis showed that SWC has a positive effect and SBD has a negative influence on the growth and yield of onion except at an appropriate value.